Indigenous, Diversity, and the Future of Human Rights in Regional Legal Systems - Yahya Ahmad Zein; Adymas Putro Utomo; Muhammad Husin Ali; Rafiq Idris; Didi Adriansyah (Journal of Human Rights, Culture and Legal System, 2025)
Indigenous peoples and cultural diversity present both opportunities and challenges for advancing human rights at the regional level. Although their rights are recognized in the constitution and under international law, the implementation of these protections remains difficult. This study aims to assess the protection of indigenous peoples’ rights within the regional legal framework. The research employs a normative juridical method, utilizing a conceptual approach, statutory analysis, and a comparative perspective with the Philippines. The findings indicate, first, that indigenous peoples in Indonesia remain vulnerable to discrimination, marginalization, and the infringement of their rights, despite constitutional and international recognition. Some regions have responded by enacting Regional Regulations to ensure that indigenous rights are acknowledged and protected. Second, the Philippines, through the National Commission on Indigenous Peoples (NCIP), has established a relatively advanced legal framework to safeguard indigenous communities. Third, the study highlights the need for a new paradigm that prioritizes effective implementation, respect for cultural diversity and local knowledge, harmonization of customary law with national and sectoral legislation, and the recognition and protection of traditional knowledge. Such a paradigm is essential to guarantee the sustainable protection of the rights of customary law communities, reduce legal conflicts, and enhance their social, economic, and cultural well-being within the regional legal system.